2023
DOI: 10.3390/healthcare11040551
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Chronic Kidney Disease of Unknown Etiology (CKDu): A Systematic Review

Abstract: (1) Background: Despite ample research, the factors, specific causes, and pathways associated with chronic kidney disease of unknown etiology (CKDu) remain elusive. Therefore, we performed a systematic review to explore the potential etiologies for the development of CKDu globally. (2) Methods: A systematic literature review was conducted using databases CINAHL, Cochrane Library, Embase, Google Scholar, MEDLINE, and PsycINFO on the specific causes and pathophysiology related to CKDu from inception until April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Exposure to heavy metals has long been known to cause renal damage and is suspected of playing a key role in recent epidemics of kidney injury, due to use of agrochemicals known to contain nephrotoxic metals and some evidence of elevated heavy metal levels in agricultural communities’ water sources. 21 , 45 , 46 , 47 , 48 , 49 Indeed, arsenic, cadmium, and lead are pervasive toxicants with established mechanisms for inducing both acute kidney injury and CKD, resulting in ongoing investigations into potential contributions to the epidemics of CKDu occurring worldwide. 50 , 51 Although some association of heavy metals have been made with increased risk of CKDu, such findings have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to heavy metals has long been known to cause renal damage and is suspected of playing a key role in recent epidemics of kidney injury, due to use of agrochemicals known to contain nephrotoxic metals and some evidence of elevated heavy metal levels in agricultural communities’ water sources. 21 , 45 , 46 , 47 , 48 , 49 Indeed, arsenic, cadmium, and lead are pervasive toxicants with established mechanisms for inducing both acute kidney injury and CKD, resulting in ongoing investigations into potential contributions to the epidemics of CKDu occurring worldwide. 50 , 51 Although some association of heavy metals have been made with increased risk of CKDu, such findings have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, many authors limit CKDu to a particular type of CKD frequently found in rural settings in non-diabetic people, accompanied by low-grade proteinuria, and a rapid transition to end-stage kidney disease (ESKD). 4,5 The atypical presentation of CKDu has become epidemic in different regions of the world, which usually remains undiagnosed until its late stage. Over the past few decades, parts of Central America, South Asia, Eastern Europe, and other countries such as Sudan, Tunisia, Tanzania, and the El-Minia Governorate in Egypt reported a similar disease pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a similar endemic was also reported, such as Balkan endemic nephropathy, Mesoamerican nephropathy, and Chinese herb nephropathy, which were named after the area of origin. 4…”
Section: Introductionmentioning
confidence: 99%
“…Potential causes include environmental or occupational exposure to nephrotoxins, heat stress, infection, and genetic predisposition. 6 , 7 , 8 The disease typically affects individuals younger than 50 years, men, and those who engage in strenuous manual labor; several regions, particularly in India and Sri Lanka, report similar disease rates in women. CKDu—or a similar disease process—can also occur in nonagricultural communities.…”
mentioning
confidence: 99%